2020
DOI: 10.1111/plb.13179
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors affecting the fitness of the threatened orchid Anacamptis robusta (Orchidaceae): Habitat disturbance, interactions with a co‐flowering rewarding orchid and hybridization events

Abstract: The food-deceptive species Anacamptis robusta is threatened in the Balearic Islands, and its habitat has recently been transformed through human disturbance. This study investigated how human disturbance affects the reproductive output of A. robusta and how its fitness is affected by competition with rewarding relatives, fungal infections and hybridization processes. • To evaluate the impact of habitat loss on plant fitness, data on reproductive measures were obtained in two well-conserved subpopulations and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…On the contrary, in S. parviflora , flower number was negatively related to fruit set. The negative correlations found in this study may be attributable to resource limitation, as reported by Capó et al (2021) and Jersáková et al (2006). However, additional research is necessary to validate this finding.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…On the contrary, in S. parviflora , flower number was negatively related to fruit set. The negative correlations found in this study may be attributable to resource limitation, as reported by Capó et al (2021) and Jersáková et al (2006). However, additional research is necessary to validate this finding.…”
Section: Discussionsupporting
confidence: 72%
“…Data are available from the Zenodo Digital Repository https://doi.org/10.5281/zenodo.7826601 (Capó et al, 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, plant morphology and population structure are also likely to be important. Parameters such as plant height, inflorescence size, flower number, spur length, population size, flowering time and canopy density have been demonstrated to affect or influence fitness (Scopece et al 2017;Capo ´et al 2020a). Thus, monitoring of the within-species variation in individual fitness is important to obtain a more realistic overview of the reproductive biology of these species.…”
Section: Introductionmentioning
confidence: 99%
“…Low mean reproductive success rates have been reported for sexually deceptive orchids ( Vandewoestijne et al 2009 ; Borràs and Cursach 2021 ), food-deceptive orchids ( Dormont et al . 2010 ; Pellegrino et al 2010 ; Claessens and Kleynen 2011 ; Capó et al 2021 ) or colour dimorphic orchids ( Pellegrino et al 2008 ; Sonne and Hauser 2014 ; Jersáková et al 2015 ). High fruit set values (above 50 up to 80 %) have been reported in natural populations of rewarding orchids ( Meekers and Honnay 2011 ; Joffard et al 2020 ; Zhang and Gao 2021 ).…”
Section: Discussionmentioning
confidence: 99%